(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Hematological studies were carried out in cattle with tongue-rolling hyperactivity in order to establish the etiopathogenetic mechanisms of this behavioral disorder. Materials and Methods: Cattle were divided into two groups: Group 1 (n = 12), control animals that did not demonstrate the tongue-rolling orosthenic activity, and Group 2 (n = 12), cattle that manifested this stereotyped behavior. Blood samples were collected from all cattle twice at 10-day intervals from Vena jugularis for analysis of red blood cell counts, hemoglobin (HGB) content, mean corpuscular volume (MCV), mean corpuscular HGB (MCH), mean corpuscular HGB concentration (MCHC), hematocrit (HCT), white blood cell counts (WBC), and differential white cell counts [lymphocytes (LYM), monocytes (MON), and granulocytes (GRAs)]. Some blood biochemical constituents were assayed: calcium, inorganic phosphorus, magnesium, plasma total protein, blood glucose, total bilirubin, urea, creatinine, chlorides, cholesterol, triglycerides, and albumin, as well as the enzyme activities of aspartate amino-transferase (AST), alanine amino-transferase (ALT), alkaline phosphatase (ALP), gamma-glutamyltransferase (γ-GT), lactate dehydrogenase (LDH), and creatine kinase (CK). Blood concentrations of the hormones adrenaline, noradrenaline, cortisol, adrenocorticotropic hormone (ACTH), dopamine, serotonin, free thyroxine, thyroid-stimulating hormone, and trace elements manganese, copper, and iron were determined. Results: It was found out that the cattle with tongue-rolling hyperactivity did not demonstrate changes in red blood picture (HGB, HCT, MCV, MCH, MCHC), white blood picture (WBC, LYM, MON, GRA), blood biochemistry (Ca, P, Mg, TP, Glu, TB, urea, creatine, Cl, Chole, TG, and Alb), AST, ALT, ALP, γ-GT, LDH, and CK activities, Cu, and Fe levels. In the study, increased concentrations of adrenaline, noradrenaline, cortisol, ACTH, and serotonin were established. Conclusion: The data demonstrating increased levels of adrenaline, noradrenaline, cortisol, and ACTH confirmed the etiological role of environmental stressors in the emergence of oral hyperactivity. Increased serotonin concentrations in the blood suggest that cattle with the stereotype are probably “happy” with tongue rolling. The lack of changes in blood trace elements manganese, copper, and iron allowed excluding their deficiency as a probable cause in the etiology of the disorder. J. Adv. Vet. Anim. Res., 10(2): 336–341, June 2023 http://doi.org/10.5455/javar.2023.j685